Penerapan Media Proyeksi dalam Pembelajaran PAI - Sibuea, Parulian; Aryanti, Dewi; Ramadhan, Habibie; Khoridatunnida, Khoridatunnida; Thoha, Muhammad Akbar; Humairah, Nabila; Pasaribu, Sriwahyuni; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2024)
This research aims to improve student activity and learning outcomes in Islamic Religious Education (PAI) subjects by implementing projection learning media. Projection media, which is a visual media, is expected to help teachers convey material more effectively and make it easier for students to understand. Through the qualitative descriptive method, student activities are observed using the observation method, while learning outcomes are measured using the question and answer method. The findings show that projection media can visualize material in a realistic way, increase student involvement, and provide support for teachers to be more creative in designing learning. It is hoped that the application of this projection media can have a positive impact on the efficiency and effectiveness of the PAI learning process, as well as creating more interesting and interactive learning conditions for students.